An underwater vehicle for cleaning dirty bottom of ships. Issue 1 (September 2020) - Zhang, Yan; Wang, Xiaojuan
Abstract: With the rapid development of Global trade, the freight volume of marine transportation is increasing. In the process of shipping, the part of the hull below the waterline is immersed in the water for a long time, marine organisms will adhere to the bottom of the ship and constantly breed, forming a dirty bottom of the ship, resulting in increased navigation resistance, fuel consumption and other hazards. The work "underwater vehicle for cleaning dirty bottom of ship" can effectively monitor the attachment condition of the bottom of the ship, clean the bottom of the ship quickly and efficiently, and detect the damage of the bottom surface. Compared with the existing cleaning devices, this work realizes remote automatic cleaning operation, and has real-time monitoring function, with high cleaning efficiency and strong adaptability.